The Effectiveness of Digital-Based Interactive Learning Videos in Increasing Interest and Basic Volleyball Movement Skills in Elementary Schools - Septiani Nirmalasari; Tatang Muhtar; Muhammad Nur Alif; Anggi Setia Lengkana (Universitas Negeri Semarang, 2026)
Low learning interest and sub optimal mastery of basic volleyball movement skills remain a recurring problem in Physical Education learning at elementary schools. In response to this challenge, this study aims to analyze the impact of digital interactive learning video presentations on increasing both learning interest and basic volleyball movement skills. More specifically, this skill evaluation includes the forearm pass, overhead pass, underhand serve, overhand serve, and spike techniques among grade five students at Rancakalong Elementary School. To achieve that goal, this quantitative study applied a preexperimental design through a one group pretest and posttest approach involving 20 students. Furthermore, the data collection process relied on a Likert scale learning interest questionnaire with a reliability value of 0.87 and a five-component performance test with a reliability value of 0.92 which was converted into a scale of zero to one hundred. After all data were collected, a comprehensive statistical analysis was conducted which included the Shapiro Wilk normality test, paired sample t test, Cohen d effect size calculation, and normalized N Gain analysis. As a result, the test proved a highly convincing increase in the learning interest domain with a t value of 53.18, an effect size of 11.89, and an N Gain score of 0.63. Not only that, but a similar positive impact was also recorded on the mastery of physical movement skills with a t value of 22.93, an effect size of 5.13, and an N Gain score of 0.38. Overall, both of these improvement achievements simultaneously occupied the moderate category. Ultimately, this series of findings further reinforces the importance of integrating interactive visual tools as an effective breakthrough in optimizing the quality of sports education at the elementary school age.